1986
DOI: 10.1007/bf01965007
|View full text |Cite
|
Sign up to set email alerts
|

The subcutaneous air pouch model of synovium and the inflammatory response to heat aggregated gammaglobulin

Abstract: Subcutaneous injection of sterile air in rodents results in the formation of an air pouch with a lining morphologically similar to synovium (Edwards et al., 1981). We extended the comparison between pouch and synovial tissue and confirmed broad similarities in structure and function but also noted important differences. The air pouch was used to study the time course of the acute inflammatory response to heat aggregated human IgG. Saline washout of the pouch allowed simultaneous measurement of cellular and med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…There was massive recruitment of cells into the pouches of animals injected with carrageenan after 6 h (from 1 × 10 7 to 11.71 × 10 7 ). At this time point, in carrageenan-treated pouches, the cells were mostly PMN and changed to a prevalence of macrophages from 48 h onwards (data not shown), as it has been reported previously [29,30]. The total number of infiltrating leukocytes in the pouch fluid was 11.16 × 10 7 at hour 72 (Fig.…”
Section: Discussionsupporting
confidence: 65%
“…There was massive recruitment of cells into the pouches of animals injected with carrageenan after 6 h (from 1 × 10 7 to 11.71 × 10 7 ). At this time point, in carrageenan-treated pouches, the cells were mostly PMN and changed to a prevalence of macrophages from 48 h onwards (data not shown), as it has been reported previously [29,30]. The total number of infiltrating leukocytes in the pouch fluid was 11.16 × 10 7 at hour 72 (Fig.…”
Section: Discussionsupporting
confidence: 65%
“…The rat air pouch is a cavity that differs from others, such as the peritoneum, by its absence of mast cells. 23 We intended to investigate whether the tested antidepressant drugs would still produce an anti-inflammatory response in the absence of these cells. We demonstrated that the effects of both carrageenan and the direct chemotactic factor fMLP were markedly inhibited by amitriptyline, clomipramine, and maprotiline.…”
Section: Discussionmentioning
confidence: 99%
“…A sign of withdrawal (convulsions on handling) here detected appeared to reach a peak at 7 h, but high values were also obtained between 6 and 11 h (data not shown), a result closely similar to the findings of previous reports (14,18). Although these results indicated that the dose was sufficiently high to produce dependence on ethanol, they do not allow the conclusion that there is a relationship between abstinence duration and changes in It has been demonstrated that carrageenan-induced neutrophil migration occurs by a process dependent on the release of chemotactic mediators by resident cells (25,26). Thus, it is possible that the inhibitory effect of ethanol on carrageenan-induced neutrophil recruitment could occur by an inhibitory action on the release of chemotactic agents such as leukotriene B 4 , TNF-α, interleukin 1 or 8 from macrophages and/or mast cells.…”
Section: Discussionmentioning
confidence: 92%